PENGALAMAN BELAJAR SISWA KELAS X PADA PEMBELAJARAN SOSIOLOGI DI SMA PGRI 2 PADANG - Fadillah, Putri; Sarbaitinil; Yuhelna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the suboptimal engagement of tenth-grade students in Sociology learning at SMA PGRI 2 Padang, which results in a less meaningful learning experience. This study aims to describe the learning experiences of tenth-grade students in Sociology and analyze the factors influencing them. This study used a qualitative, descriptive approach. Thirteen informants participated in the study: seven tenth-grade students as the primary subjects, one Sociology teacher, and five parents as supporting informants. Data collection techniques included non-participant observation, in-depth interviews, and documentation studies. Data were analyzed using the Miles and Huberman model, comprising the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that students' learning experiences in Sociology are still suboptimal. This is characterized by low active student participation, a predominance of lecture methods, a lack of varied learning media, and a less conducive classroom atmosphere. Factors influencing students' learning experiences include internal factors such as student motivation and self-confidence, as well as external factors such as learning methods, teacher-student interaction, and classroom management. This study concludes that meaningful learning experiences require more interactive, contextual, and participatory learning strategies to increase student involvement and understanding in Sociology learning.